2010
DOI: 10.5194/acp-10-6169-2010
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene nitrates: preparation, separation, identification, yields, and atmospheric chemistry

Abstract: Abstract.Isoprene is an important atmospheric volatile organic compound involved in ozone production and NO x (NO+NO 2 ) sequestration and transport. Isoprene reaction with OH in the presence of NO can form either isoprene hydroxy nitrates ("isoprene nitrates") or convert NO to NO 2 which can photolyze to form ozone. While it has been shown that isoprene nitrate production can represent an important sink for NO x in forest impacted environments, there is little experimental knowledge of the relative importance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
160
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(173 citation statements)
references
References 37 publications
(78 reference statements)
9
160
4
Order By: Relevance
“…In CheT2, the overall yield of NO x from ISON was increased, in line with recent measurements (Perring et al, 2009), by increasing the ISON photolysis rate and adding an ISON + OH → NO 2 reaction channel. O 3 initiated degradation of ISON was also added based on the evidence of Lockwood et al (2010) -it should be noted, however, that Lee et al (2014) found that Lockwood et al (2010) substantially overestimated the rate of this reaction. Secondly, CheT2 includes the formation of hydroperoxy-aldehydes (HPALDs) from ISO 2 and subsequent rapid release of OH (Peeters et al, 2009).…”
Section: Isoprene Chemical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In CheT2, the overall yield of NO x from ISON was increased, in line with recent measurements (Perring et al, 2009), by increasing the ISON photolysis rate and adding an ISON + OH → NO 2 reaction channel. O 3 initiated degradation of ISON was also added based on the evidence of Lockwood et al (2010) -it should be noted, however, that Lee et al (2014) found that Lockwood et al (2010) substantially overestimated the rate of this reaction. Secondly, CheT2 includes the formation of hydroperoxy-aldehydes (HPALDs) from ISO 2 and subsequent rapid release of OH (Peeters et al, 2009).…”
Section: Isoprene Chemical Mechanismsmentioning
confidence: 99%
“…Fourth, dry deposition of isoprene nitrates, which may represent an important NO x sink O. J. Squire et al: Influence of isoprene chemical mechanism on modelled tropospheric ozone 5125 in isoprene-rich regions, is also uncertain, with measured deposition velocities ranging from 0.4 cm s −1 (Shepson et al, 1996) to 2.7 cm s −1 (Farmer and Cohen, 2008). Finally, there is evidence for the importance of O 3 -initiated isoprene nitrate degradation (Lockwood et al, 2010) and fast photolysis of isoprene nitrates (Müller et al, 2014). In this study, the isoprene schemes we compare have a range of different parameterisations for isoprene nitrates.…”
mentioning
confidence: 99%
“…Here we provide a brief overview of the chemical mechanism which is based on RACM2 chemistry Stockwell et al, 2010) with substantial modifications to the RONO 2 and isoprene chemistry. The isoprene chemistry is based on Paulot et al (2009a, b) and uses ozonolysis rates of isoprene-derived nitrates from Lockwood et al (2010). The formation of a hydroperoxyaldehyde (HPALD) from the 1,6 H-shift of isoprene peroxy radicals is included using the rate constant measured by Crounse et al (2011).…”
Section: B2 Chemical Mechanismmentioning
confidence: 99%
“…Seven different chemically distinct compounds based on the isoprene carbon backbone, containing epoxy, alcohol, nitrate, and/or sulfate functional groups, have now been identified in ambient SOA Claeys et al, 2004;Wang et al, 2005;Surratt et al, 2007;Altieri et al, 2009;Gómez-González et al, 2008;Surratt et al, 2008;Froyd et al, 2010). Some of these compounds are undoubtedly formed from gas phase processing (Perring et al, 2009a, b;Lockwood et al, 2010;Ng et al, 2008), of isoprene, while other compounds (such as organosulfates) clearly indicate that additional chemical processing is occurring on ambient SOA particles themselves (Cole-Filipiak et al, 2010;Paulot et al, 2009;Surratt et al, 2010;Chan et al, 2010;Minerath et al, 2008Eddingsaas et al, 2010;Szmigielski et al, 2010;Nozière et al, 2010;Rudzinski et al, 2009) We recently investigated some of the potential SOA-phase chemistry for isoprene-related compounds, and proposed an overall mechanism (shown in Fig. 1) that can rationalize the existence of five of the seven observed isoprene-derived SOA components (Darer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%